From antioxidant to muscle enhancer: Resveratrol's role in grass carp (Ctenopharyngodon idella) nutrition - Xi-Dong Xie; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Rui-Nan Zhang; Xiao-Qiu Zhou (Aquaculture Reports)
Resveratrol (RES), a type of stilbenoid, is known for its significant role in enhancing meat quality by virtue of activating SIRT1. Against this backdrop, this study explored the impact of resveratrol on various parameters influencing flesh quality in adult grass carp. Over a span of 9 weeks, adult grass carp were fed diets with five different levels of RES (0, 40, 80, 160 and 320 mg/kg). Our findings demonstrated that resveratrol supplementation had no adverse effects on the growth performance of adult grass carp. Notably, adding the right amount of resveratrol to the diets caused the protein and amino acid levels, pH24 h, and shear force of grass carp muscle to rise. Additionally, it led to a reduction in cooking loss and lactic acid content. Moreover, Addition of appropriate levels of resveratrol to the feed promoted myofiber hyperplasia in adult grass carp, which may be achieved by stimulating adult myoblast proliferation and differentiation. Subsequent studies have found that appropriate levels of resveratrol inhibit endoplasmic reticulum stress (ERS), which promotes muscle fiber development. Additionally, resveratrol was found to lead to an increase in unsaturated fatty acid (UFA) content in grass carp muscle. This alteration in fatty acid composition could be attributed to changes in fatty acid transport, synthesis, and catabolism. According to muscle protein carbonyl level, muscle protein content and frequency of muscle fibers smaller than 20 μm, the optimum resveratrol supplementations of grass carp were 178.33, 198.33 and 226.67 mg/kg.